2019
DOI: 10.1002/cssc.201901739
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated Ionic‐Liquid‐Based Electrolytes for High‐Voltage Lithium Batteries with Improved Performance at Room Temperature

Abstract: Ionic liquids (ILs) have been widely explored as alternative electrolytes to combat the safety issues associated with conventional organic electrolytes. However, hindered by their relatively high viscosity, the electrochemical performances of IL‐based cells are generally assessed at medium‐to‐high temperature and limited cycling rate. A suitable combination of alkoxy‐functionalized cations with asymmetric imide anions can effectively lower the lattice energy and improve the fluidity of the IL material. The Li/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 52 publications
6
57
0
Order By: Relevance
“…Further, the activation energy for ion conduction ( E a ic , Figure 2c) can be deduced from Vogel–Tammann–Fulcher (VTF) analysis (Table S1, Supporting Information), indicating that LCIL exhibited a lower activation energy (5.3 kJ mol −1 ) than DIL and CIL (5.9 and 6.7 kJ mol −1 , respectively). These findings may be attributed to alterations in the conduction mechanism [ 6b,17 ] or nanoscale heterogeneity in the solution structure. [ 18 ]…”
Section: Resultsmentioning
confidence: 99%
“…Further, the activation energy for ion conduction ( E a ic , Figure 2c) can be deduced from Vogel–Tammann–Fulcher (VTF) analysis (Table S1, Supporting Information), indicating that LCIL exhibited a lower activation energy (5.3 kJ mol −1 ) than DIL and CIL (5.9 and 6.7 kJ mol −1 , respectively). These findings may be attributed to alterations in the conduction mechanism [ 6b,17 ] or nanoscale heterogeneity in the solution structure. [ 18 ]…”
Section: Resultsmentioning
confidence: 99%
“…According to the generally accepted definition [28], ILs are organic-organic or organic-inorganic salts that are liquids at temperatures below 100 • C. ILs have been widely used, mainly as catalysts and solvents in the synthesis of organic compounds [29] and polymers [30], including in mixtures with supercritical CO 2 [31], vulcanization accelerators for rubber [32], and also as electrolytes [33][34][35][36][37][38], specifically for lithium batteries [39][40][41][42][43][44][45][46][47]. A comprehensive literature review concerning ILs in polymer systems was published [48], and the role of ILs in lithium ion batteries was explained in detail in another review [49].…”
Section: Introductionmentioning
confidence: 99%
“…27 The introduction of alkoxy group in the IL's cation structure is known to lower the lattice energy and reduce/ suppress the crystallization of neat ILs as well as IL-based solutions. 28 Indeed, the crystallization of the Pyr 1201 TFSI electrolytes is effectively suppressed while the solubility of Ca(TFSI) 2 is slightly increased to 5 mol%. In the thermograms of Pyr 1201 TFSI with and without Ca-salt ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Substitution of the alkyl-functionalized pyrrolidinium cation with the alkoxyfunctionalized ammonium cation has been shown to reduce the lattice energy and suppress crystallization of the IL solution. Correspondingly, the crystals obtained from N 01 TFSI electrolyte are more fragile than those from [Pyr 1201 ] 2 [Ca(TFSI) 4 ], which makes it impossible to obtain a meaningful XRD analysis.Previous studies about Mg have demonstrated that the nature of the Mg 2+ -ion species is one of the keys to successful Mg deposition/dissolution in IL media 28. For IL-based electrolytes containing only TFSI À anion, Mg ions are typically found as Mg(TFSI) 3À 25,36.…”
mentioning
confidence: 99%